Mightier than the Sword: Polish Independent Publishing, 1976-1989 - Doucette, Siobhan (2013)
This dissertation analyzes the rapid growth of Polish independent publishing between 1976 and 1989, examining the ways in which publications were produced as well as their content. Widespread, long-lasting independent publishing efforts were first produced by individuals connected to the democratic opposition; particularly those associated with KOR and ROPCiO. Independent publishing expanded dramatically during the Solidarity-era when most publications were linked to Solidarity, Rural Solidarity or NZS. By the mid-1980s, independent publishing obtained new levels of pluralism and diversity as publications were produced through a bevy of independent social milieus across every segment of society